Cardiorenal disease management in type 2 diabetes: An expert consensus. Issue 12 (December 2022) - Mohan, Viswanathan; Singh, Awadhesh Kumar; Zargar, Abdul Hamid; Almeida, Alan; Bhalla, Anil Kumar; Mohan, Jagadish Chander; Dalal, Jamshed; Sahay, Manisha; Mohanan, Padhinhare P.; Maitra, Sanjay; Ghosh, Sujoy; Jeloka, Tarun; et al.
Abstract: Background and aim: The interplay between cardiovascular disease (CVD), chronic kidney disease (CKD) and type 2 diabetes (T2D) is well established. We aim at providing an evidence-based expert opinion regarding the prevention and treatment of both heart failure (HF) and renal complications in people with T2D. Method: ology: The consensus recommendations were developed by subject experts in endocrinology, cardiology, and nephrology. The criteria for consensus were set to statements with ≥80% of agreement among clinicians specialized in endocrinology, cardiology, and nephrology. Key expert opinions were formulated based on scientific evidence and clinical judgment. Results: Assessing the risk factors of CVD or CKD in people with diabetes and taking measures to prevent HF or kidney disease are essential. Known CVD or CKD among people with diabetes confers a very high risk for recurrent CVD. Metformin plus lifestyle modification should be the first-line therapy (unless contraindicated) for the management of T2D. Glucagon-like peptide 1 (GLP-1) agonists can be preferred in people with atherosclerotic cardiovascular disease (ASCVD) or with high-risk indicators, along with sodium–glucose cotransporter-2 inhibitors (SGLT2i), whereas SGLT2i are the first choice in HF and CKD. The GLP-1 agonists can be used in people with CKD if SGLT2i are not tolerated. Conclusion: Current e vidence suggests SGLT2i as preferred agents among people with T2D and HF, and for those with T2D and ASCVD. SGLT2i and GLP-1RA also lower CV outcomes in those with diabetes and ASCVD, and the treatment choice should depend on the patient profile. Key Highlights: Metformin plus lifestyle modification is the first-line therapy (unless contraindicated) for the management of T2D. SGLT2i should be preferred in most patients with atherosclerotic cardiovascular disease. GLP-1RAs may be preferred in those with prior stroke or evidence of atherosclerotic disease. SGLT2i are the first choice in heart failure and CKD. GLP-1 agonists can be used in people with CKD if SGLT2i are not tolerated.